Iron, zinc and phytic acid retention of biofortified, low phytic acid, and conventional bean varieties when preparing common household recipes - Hummel, Marijke; Talsma, Elise F.; Taleon, Victor; Londoño Hernandez, Luis Fernando; Brychkova, Galina; Gallego, Sonia; Raatz, Bodo; Spillane, Charles (MDPI, 2020)
Biofortification is an effective method to improve the nutritional content of crops and nutritional intake. Breeding for higher micronutrient mineral content in beans is correlated with an increase in phytic acid, a main inhibitor of mineral absorption in humans. Low phytic acid (lpa) beans have a 90% lower phytic acid content compared to conventional beans. This is the first study to investigate mineral and total phytic acid retention after preparing common household recipes from conventional, biofortified and lpa beans. Mineral retention was determined for two conventional, three biofortified and two lpa bean genotypes. Treatments included soaking, boiling (boiled beans) and refrying (bean paste). The average true retention of iron after boiling was 77.2–91.3%; for zinc 41.2–84.0%; and for phytic acid 49.9–85.9%. Soaking led to a significant decrease in zinc and total phytic acid after boiling and refrying, whereas for iron no significant differences were found. lpa beans did not exhibit a consistent pattern of difference in iron and phytic acid retention compared to the other groups of beans. However, lpa beans had a significantly lower retention of zinc compared to conventional and biofortified varieties (p < 0.05). More research is needed to understand the underlying factors responsible for the differences in retention between the groups of beans, especially the low retention of zinc. Combining the lpa and biofortification traits could further improve the nutritional benefits of biofortified beans, by decreasing the phytic acid:iron and zinc ratio in beans.